Clinical evaluation and biochemical analyses of thiamine deficiency in Pacific harbor seals (Phoca vitulina) maintained at a zoological facility. - Croft, Lara; Napoli, Eleonora; Hung, Connie K; St Leger, Judy; Gearhart, Scott; Heym, Kathy; Wong, Sarah; Sakaguchi, Danielle; Lin, Alex; Puschner, Birgit; Giulivi, Cecilia (Journal of the American Veterinary Medical Association, 2013)
ObjectiveTo determine thiamine-dependent enzyme activities in various tissue samples of Pacific harbor seals (Phoca vitulina) and thiaminase activities in dietary fish.DesignCross-sectional study.Animals11 Pacific harbor seals with thiamine deficiency and 5 control seals.ProceduresSeals underwent evaluation to rule out various diseases and exposure to toxins. For seals that died, measurement of thiamine-dependent enzymes in liver and brain samples and determination of mitochondrial DNA (mtDNA) copy number in liver, brain, and muscle samples were performed. Thiaminase activity in dietary fish was determined.Results8 seals with thiamine deficiency died. Affected seals typically had acute neurologic signs with few nonspecific findings detected by means of clinicopathologic tests and histologic examination of tissue samples. Thiamine-dependent enzyme activities in liver samples of affected seals were significantly lower than those in control liver samples. The primary activation ratios and latencies for enzymes indicated that brain tissue was more affected by thiamine deficiency than liver tissue. Activities of pyruvate dehydrogenase were more affected by thiamine deficiency than those of transketolase and ketoglutarate dehydrogenase. For control seals, the mtDNA copy number in muscle samples was significantly lower than that for affected seals; conversely, the copy number in control liver samples was significantly greater than that of affected seals. Thiaminase activity was substantially higher in smelt than it was in other types of dietary fish.Conclusions and clinical relevanceResults of analyses in this study confirmed a diagnosis of thiamine deficiency for affected seals resulting from high thiaminase activity in dietary fish, inadequate vitamin administration, and increased thiamine demand caused by pregnancy and lactation.